Profil RBC, WBC, HCT, Dan HGB Domba Ekor Tipis Pada Periode Kebuntingan Dan Pasca Partus: RBC, WBC, HCT, And HGB Profile of Thin-Tailed Sheep During Pregnancy And Postpartum Periods - Kalandara, Dhinta Maulidya; Hidayat, Muhammad Taufik; Ryanto, Richard Renaldy; Habibullah, Muhammad Raihan Rafi; Ridlo, Muhammad Rosyid (Fakultas Peternakan Universitas Jambi, 2025)
Background: Hematology analysis studies on thin-tailed sheep (TET) are a strategic field in studying livestock health and reproduction. However, the hematological profile during pregnancy and postpartum has not been extensively studied. Meanwhile, knowledge of the dynamics of hematological parameters is very important as it serves as the basis for optimal livestock health and reproductive management. Purpose: This study investigates the changes in hematological blood parameters during pregnancy and the postpartum period, including White Blood Cell (WBC), Red Blood Cell (RBC), hemoglobin (HGB), and hematocrit (HCT). Methods: Blood sampling was performed on 5 pregnant DET animals and 5 post-partum DET animals, with samples taken from the jugular vein using a 6 ml syringe for a total of 2.5 ml. The blood was then placed into an EDTA vacutainer tube, and hematological analysis was subsequently conducted using the Licare Vet Auto Hematology Analyzer CC-3200 in the laboratory of the Veterinary Technology Study Program, Vocational School Gadjah Mada University. Results: The results of statistical analysis showed that there were significant differences (P < 0.05) in WBC, RBC, HGB and HCT parameters between postpartum and pregnant ewes. The results showed that WBC values increased significantly in postpartum ewes (51.78 ± 19.24 x 10⁹/L) compared to pregnant ewes (40.54 ± 9.12 x 10⁹/L), reflecting high immunological activity due to physiological stress and the risk of postpartum infection. RBC parameters showed a slight decrease during pregnancy (9.024 ± 0.69 x 10¹²/L) compared to the postpartum period (9.554 ± 1.20 x 10¹²/L), which was thought to be due to hemodilution. HGB levels remained within the normal range, although they decreased in ewes during pregnancy (89.00 ± 7.31 g/L) compared to postpartum (92.00 ± 16.43 g/L). HCT showed a significant decrease both during pregnancy (20.84 ± 2.55%) and postpartum (21.72 ± 2.94%), below the normal range due to hemodilution and blood loss during delivery. Conclusion: Overall, these studies indicate significant hematological adaptations during pregnancy and postpartum to meet metabolic and physiological requirements.